Automatic Segmentation And Detection Of Mass In Digital Mammograms - Mat Isa, Nor Ashidi; Ting, Shyue Siong (2012)
This paper presents an automated system for mass segmentation and detection in mammograms. Initially, breast segmentation is applied to separate the breast and non-breast area. Then, image enhancement is employed to improve the contrast of the tissues structure in mammograms. Finally, constraint region growing based on local statistical texture analysis is applied to detect and segment out the mass from the mammograms.